2019
DOI: 10.3390/sports7070171
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Perceived Performance Among Junior Athletes—Associations with Affective and Cognitive Components of Stress

Abstract: The current study investigated associations between cognitive components such as psychological resilience and perceived stress, and affective components such as positive and negative affect, and athlete burnout and perceived performance among 670 Norwegian junior athletes attending high schools specialized for sports. A hypothesized model of the relations between the constructs was analyzed by structural equation modeling (SEM). The results in the current study show that athlete resilience is a key in understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
0
26
0
3
Order By: Relevance
“…Briefly, in an athletic environment, burnout syndrome can be defined as a syndrome comprised of three symptoms: (i) physical and emotional exhaustion, (ii) a reduced sense of accomplishment, and (iii) sport devaluation [50]. The prevalence of burnout has become a serious issue, especially among young adolescent athletes [51,52,53]. With regard to fact that the onset of intensive training was found to be a significant correlate of PDB only in females, it is interesting that previous studies identified higher levels of burnout among females [54].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, in an athletic environment, burnout syndrome can be defined as a syndrome comprised of three symptoms: (i) physical and emotional exhaustion, (ii) a reduced sense of accomplishment, and (iii) sport devaluation [50]. The prevalence of burnout has become a serious issue, especially among young adolescent athletes [51,52,53]. With regard to fact that the onset of intensive training was found to be a significant correlate of PDB only in females, it is interesting that previous studies identified higher levels of burnout among females [54].…”
Section: Discussionmentioning
confidence: 99%
“…Daily training and competitions represent the main physiological load expositions. However, school tasks, social interactions, and the additional physical activities to the training routine, determine a cumulative high-level physio-psychological workload and potentially, an increased fatigue perception [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stressors encountered in sport are most often subjective rather than objective and universal, and accordingly, the nature of the stress response is mostly determined by the athlete’s personal interpretation [29]. It then follows that any factor that influences the cognitive appraisals of stressors is likely to affect the balance between eustress and distress and, thus, contribute to determine an athlete’s susceptibility to burnout.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of intra- and interpersonal factors may help athletes adapt to the stressors and setbacks encountered in sports [26,28], and protective factors have further been suggested to operate by influencing athletes’ challenge appraisal and meta-cognitions [26]. Accordingly, the psychological response to stress is subjective and likely to be determined by cognitive appraisal processes [29].…”
Section: Introductionmentioning
confidence: 99%